Seismic response of three-dimensional r - Magliulo, Gennaro (Earthquake engineering & structural dynamics.)
This paper deals with seismic analysis of plan-asymmetric r/c frame multi-storey buildings. Non-linear numerical analyses are carried out by using a lumped plasticity model for beams and a multi-spring model for columns, the latter one introduced to account for axial force?biaxial bending moment interaction. A comparison between numerical analyses and experimental test results is reported in order to calibrate the numerical model, showing that the adopted model is very suitable. In order to study the effects of the earthquake orthogonal component, the seismic response of the modelled structure under uni-directional excitation is compared to the one under bi-directional excitation. Such comparison shows that the maximum base shear and the top displacement are not very sensitive to the presence of the orthogonal component, which, conversely, leads to large increase in the column plastic excursions.